Ukraine Crisis and its impact on Regional Security Environment - Ms. Farzana Siddique (CISS Insight Journal, 2014)
Events unfolding in East Europe are transforming the security environment in the region as political instability in Ukraine and Crimea’s annexation by Russia has impacted the region deeply. President Yanukovych’s government collapsed in Ukraine, in February 2014 in the wake of large scale protests against his decision to join NATO and European Union. Growing political unrest in Ukraine, the mobilization of Russian forces in eastern Ukraine and Crimea’s annexation by Russia are important developments. They are all occurring in a neighborhood where interests of several states overlap and are likely to shape the future security environment in the whole region.Crisis erupted in Ukraine when protestors came out in the streets in Kiev against the government due to some political and economic reforms and foreign policy shift towards the western countries. The government of Yanukovych was toppled and he was forced to get asylum in Crimea. Political unrest in Ukraine and coming up of pro-western government in power in the country prompted Russia, which is the neighbor of Ukraine and has strategic interest in it, to annex Crimea. It may also be mentioned that a sizable portion of Ukrainian population is of Russian origin. They were inclined to support Russia against the new government’s policies towards making Ukraine a part of western security and economic system. The article analyses causes of current Ukraine crisis along with the Russian annexation of Crimea and how these developments affect the security situation of the region.